The aggressive behavior of Nile tilapia introduced into novel environments with variation in enrichment - Barreto, Rodrigo E. [UNESP]; Arantes Carvalho, Graziele G. [UNESP]; Volpato, Gilson Luiz [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
Many studies show environmental enrichment is correlated with benefits to captive animals; however, one should not always assume this positive relationship given that enrichment increases the amount of resources that a territorial animal must defend and possibly affects its aggressive dynamics. In this study, we tested if environmental enrichment affects aggressive interactions in the aggressive fish Nile tilapia (Oreochromis niloticus). We compared fights staged between pairs of male tilapia of similar size (= matched in resource holding potential) in a novel arena that was either barren or enriched, to examine whether enrichment enhances territory value in line with theoretical predictions, with the potential for compromised welfare. We evaluated time elapsed until the first attack (latency), frequency of aggressive interactions and fight duration. We detected fight dynamic differences at the pair level. Higher resource value generated increased aggression but had no effect on fight duration or latency. This conclusion is in line with game theory predictions concerning resource value and contradicts the theory that enrichment of the environment will serve welfare purposes. (C) 2010 Elsevier GmbH. All rights reserved.
Keywords: Aggression; Agonistic profile; Environmental complexity; Fighting asymmetry; Oreochromis niloticus